The growth-poverty convergence agenda: Optimizing social expenditures to maximize their impact on agricultural labor productivity, growth, and poverty reduction in Africa - Badiane, Ousmane; Ulimwengu, John M. (International Food Policy Research Institute, 2009)
The need to achieve the Millennium Development Goals (MDGs) has raised the profile of social sector investments in Africa and other developing countries. As a result, many African countries are pressured to emphasize short-term concerns related to the symptoms of poverty at the expense of the longer-term needs to raise productivity and incomes, and thereby tackle the real roots of poverty. Because of scarce budget resources, there is a major challenge for African governments in terms of ensuring the necessary consistency of policies and strategies to promote long-term economic growth, raise smallholder productivity, achieve food security, and reduce poverty, while providing the social services that respond to immediate welfare requirements. The main objective of the convergence agenda exposed in this paper is to identify strategies that would allow developing countries to improve the management of public expenditures so as to raise the chances of meeting the income growth and social needs of their populations under tight budget constraints. In this paper we have (1) discussed the terminology used in describing the problem being studied and formulated the assumptions and hypotheses underlying the research; (2) defined a typology of growth–poverty pathways; (3) developed metrics to measure the strength of the relationship between growth and poverty reduction; (4) laid out the theory for the measurement of the degree of convergence of public expenditures on social services, that is, the extent to which they are optimized with respect to their impact on labor productivity and growth; and (5) outlined models for (a) the quantification of social services availability at the local level using a single-score concept, (b) the evaluation of the quality and efficiency of public expenditures in social services sectors in rural areas, and (c) the optimization of public expenditures allocation to maximize the impact on growth and poverty reduction; as well as (6) provided initial evidence proving the validity of the theory of convergence.